Implementation of Mindfulness Techniques Through Group Counseling Services to Reduce Stress Disorders in Final Year Guidance and Counseling Students - Amalya, Naisatul; Khaira, Wanty (Pusdikra Publishing, 2025)
Final year students often experience academic stress caused by the pressure of completing their thesis, dynamics in the guidance process with lecturers, repeated revisions, and demands to graduate within a certain time frame. This pressure often has an impact on psychological disorders such as anxiety, mental fatigue, and even decreased academic motivation. Therefore, an appropriate intervention approach is needed to help students manage stress in a healthy way. One approach that has proven effective is the mindfulness technique, which is the practice of full awareness of current experiences without negative judgment. This study aims to determine the effectiveness of the mindfulness technique applied in group counseling services on reducing the level of academic stress in final year students of the Guidance and Counseling Study Program. This study used a quantitative approach with a pre-experimental design of one group pretest-posttest design. The sample consisted of 7 students selected by purposive sampling with criteria of moderate to high stress levels. The instrument used was an academic stress scale compiled based on three aspects, namely biological and psychological. The intervention was carried out through three mindfulness-based group counseling sessions which included conscious breathing exercises, the STOP technique, awareness of thoughts and emotions, and group reflection. using paired sample t-test showed a value of t = 3.894 with a significance of p = 0.008 (p < 0.05), which indicates a significant difference between the pretest and posttest scores. The average academic stress score decreased from 87.60 to 64.71, indicating that the intervention had a significant positive effect. Thus, it can be concluded that mindfulness-based group counseling services are effective in reducing academic stress levels, strengthening emotional regulation, and supporting the psychological well-being of final year students during the completion of their studies.